The Effect of Tax Avoidance, Harmonization of Tax Regulations and Understanding of Taxation on Taxpayer Compliance with Risk Preference as a Moderation Variable in MSMEs in Makassar City - Muhammad Nuryamin Akbar Khairullah; Darwis Lannai; Hajering Hajering (Jurnal Riset Perpajakan: Amnesty, 2024)
MSMEs have an important role in Indonesia's economic growth, especially through their contribution to tax revenue, improving public welfare, and increasing investment and infrastructure development. This study aims to understand the extent of the influence of tax avoidance practices, changes in tax regulations, and understanding of taxation on MSME taxpayer compliance, especially in the context of risk preferences. The MSMEs in Makassar City who were willing to participate as respondents and who were registered as taxable entrepreneurs provided the data for this study. This study included primary and secondary data collection methods, involving direct field research with 60 respondents who completed questionnaires and statement sheets. Data analysis techniques are carried out by descriptive statistical analysis and PLS (Partial Least Square). The results showed that Tax avoidance, Harmonization of tax regulations and Understanding of Taxation had a positive and significant effect on the compliance of MSME taxpayers in Makassar City. Tax avoidance and harmonization of tax regulations have a positive and significant effect on taxpayer compliance strengthened Risk preference and Understanding of taxation is not significant on taxpayer compliance moderated by risk preference.